Strategy for marine ecotourism development based on natural resource management: Case study in Kotania Bay, Western Seram District, Maluku, Indonesia - Henderina Lelloltery; Maman Rumanta; Rony Marsyal Kunda (Nusantara Bioscience, 2021)
Abstract. Lelloltery H, Rumanta M, Kunda RM. 2021. Strategy for marine ecotourism development based on natural resource management: Case study in Kotania Bay, Western Seram District, Maluku. Nusantara Bioscience 13: 91-99. The study aimed to identify the potential for marine ecotourism in Kotania Bay, and formulated strategies and priorities for developing marine ecotourism in Kotania Bay. Data collection on ecological potential consisted of mangrove and fauna vegetation using the line transect method, while coastal and marine resources included coral reefs and reef fish using the Line Intercept Transect (LIT) method. Development strategies and priorities used the SWOT and AHP methods. The results showed that the potential of coastal natural resources around the Kotania Bay consisted of 12 mangrove species belonging to7 families with species diversity index 1.76, and dominated by Rhizophora mucronata and Bruguiera cylindrica. The bird species were 33 species belonging to 23 families, with several endemic species such as Philemon subcorniculatus, Eulipoa wallacei, Birgus latro, and Pteropus melanopogon. Potential marine water resources consisted of 45 coral species belonging to 23 genera and 14 families with 10-12 life-forms. The diversity of reef fish species was quite abundant consisting of 129 species from 60 genera and 22 families. The sand beach on Marsegu island is a tourist destination that is demanded by the tourists. SWOT analysis showed that the potential of coastal and marine natural resources in Kotania Bay is very likely to be developed as marine ecotourism.